The role of the rectus sheath block in modern perioperative care for midline laparotomy: a review of the evidence - Abbawy, Marcus; Okoh, David; Binuraj, Arundhati; Holden, Finlay; Fox, Benjamin; Sachdeva, Rajneesh; Pooni, Jagtar; Singh, Manpreet; Allen, Thomas; Ganguly, Saibal; Gao-Smith, Fang; Veenith, Tonny (Frontiers in Anesthesiology, 2026)
Perioperative management of pain is crucial in optimising patient outcomes after laparotomy. This review focuses on the rectus sheath block (RSB) and its use in midline laparotomies. This article will examine the current evidence on the clinical efficacy of this method, comparing it to alternative anaesthetic methods and outlining the numerous benefits of its use. The future of the RSB is considered, with an emphasis on where advancements may be achieved and the areas that require further research. We refer to the complications associated with RSB, which are uncommon. If a rectus sheath block is performed in accordance with the evidence-based steps outlined in this review, the likelihood of complications should be minimal.